Eco Enzyme : Pemanfaatan Limbah Rumah Tangga untuk Alternatif Pengelolaan Sampah - Dian Milasari; Eris Tiyanti; Arofa Arofa; Muhammad Syaikhon; Naura Kaulam Fadhila; Leni Rosita; Rizqy Robby Yuliyanto; Putri Laras Asri; Inu Yolanda; Bunga Sekar Melati; Fendy Setiawan; Irfan Ramadhani; Abyan Yurdin Kamal (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
Household waste remains a major environmental issue in Indonesia due to population growth and changing consumption patterns. National data indicate that household waste dominates overall waste generation, with food waste as the largest component. Improper waste management poses serious risks to environmental sustainability and public health. One simple and community-based alternative for managing organic household waste is eco-enzyme production. This community service activity aimed to enhance community awareness and participation in household waste management through eco-enzyme production. The activity was conducted in Poncol Village using socialization, hands-on practice, and community assistance methods. The results showed that the community gained sufficient understanding of the eco-enzyme production process and was able to utilize organic household waste more effectively. Successful fermentation was indicated by a brownish liquid color and a distinctive fermented aroma. This activity positively contributed to environmental awareness and demonstrated the potential of eco-enzyme as a sustainable community-based waste management solution.